Perngaruh Kondisi Soisal Ekonomi Orang Tua, Teman Sebaya dan Peran Guru Bimbingan Konseling terhadap Minat Melanjutkan Studi ke Perguruan Tinggi Siswa Kelas XI SMAN 1 Kauman - Agustin, Happy Nur; Umami, Nailariza (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Higher education plays an important role in preparing a generation that is able to compete in the global era. However, not all students are interested in continuing their studies to college, one of which is influenced by external factors. Students' interest in continuing their studies to college is an important concern in the world of education, especially at the high school level. Based on the results of initial observations at SMAN 1 Kauman, it was found that only 37.3% of grade XI students were interested in continuing their studies, while 62.7% chose to work directly or start a business. This is influenced by several factors, such as the economic conditions of parents, the influence of peers, and the role of guidance and counseling teachers. This study aims to determine the influence of the socio-economic conditions of parents, peers, and the role of guidance and counseling (BK) teachers on the interest in continuing their studies of grade XI students at SMAN 1 Kauman. This study uses a quantitative approach with multiple linear regression analysis techniques. The results of the study showed that partially, the Socioeconomic Conditions of Parents (X₁) have a positive and significant effect on Interest in Continuing Studies (Y), obtained a calculated t value = 9.557> t table = 1.971, with a significance level of 0.000 <0.05. Peers (X₂) also have a positive and significant effect on student interest, obtained a calculated t = 9.348> t table = 1.971, with a significance of 0.000 <0.05. Likewise, the Role of BK Teachers (X₃), has the greatest positive and significant effect, obtained a calculated t = 17.222> t table = 1.971, with a significance of 0.000 <0.05. Simultaneously, the three variables have a significant effect on Interest in Continuing Studies with a calculated F value = 166.965 > F table = 2.65, and a significance of 0.000 < 0.05. The coefficient of determination (R²) value is 0.710, meaning that 71% of the variation in student interest is influenced by the three variables, while the remaining 29% is influenced by other factors not studied. The interpretation of these results shows that students who have parents with better economic conditions tend to have stronger financial and psychological support to continue their education. A positive peer environment also provides motivation and emotional support, while BK teachers play an important role in providing information, direction, and shaping students' awareness of the importance of higher education. These three factors together show a real contribution in shaping students' interest in making educational decisions to college level. Based on these results, it can be concluded that the Socio-Economic Conditions of Parents, Peers, and the Role of BK Teachers have a significant effect on Interest in Continuing Studies to College in grade XI students of SMAN 1 Kauman.